Marine scientific research in Pacific Small Island Developing States. (September 2018) - Salpin, Charlotte; Onwuasoanya, Vita; Bourrel, Marie; Swaddling, Alison
Abstract: Promoting the study of the marine environment is one of the objectives of the United Nations Convention on the Law of the Sea (UNCLOS or the Convention), which constitutes the first comprehensive multilateral agreement covering all ocean spaces and embodying the concept of sustainable development by addressing all dimensions of ocean uses, including environmental, economic and social. At the core of the provisions of UNCLOS related to marine scientific research (MSR) lie the promotion of such research, international cooperation and the creation of favourable conditions for the conduct of MSR, as well as the publication and dissemination of information and knowledge resulting from such research. For Pacific Small Island Developing States (PSIDS), the ability to undertake and benefit from MSR and access appropriate technology represents a unique opportunity to contribute significantly to their sustainable development aspirations. However, many challenges remain for PSIDS to fully benefit from MSR and the opportunities associated with the development of a 'Blue Economy'. This article reviews the challenges and opportunities for PSIDS arising from MSR, including with regard to the implementation of the relevant provisions of UNCLOS. Highlights: MSR is a critical underpinning of sustainable development, including for PSIDS. Many challenges remain for PSIDS to fully benefit from MSR. Addressing such challenges would allow PSIDS to benefit sustainably from a 'Blue Economy'.